Aberrant deposition of stress granule-resident proteins linked to C9orf72-associated TDP-43 proteinopathy - Chew, Jeannie; Cook, Casey; Gendron, Tania F.; Jansen-West, Karen; del Rosso, Giulia; Daughrity, Lillian M.; Castanedes-Casey, Monica; Kurti, Aishe; Stankowski, Jeannette N.; Disney, Matthew D.; Rothstein, Jeffrey D.; Dickson, Dennis W.; et al. (Molecular neurodegeneration, 2019)
A G C hexanucleotide repeat expansion in the noncoding region of C9orf72 is the major genetic cause of frontotemporal dementia and amyotrophic lateral sclerosis (c9FTD/ALS). Putative disease mechanisms underlying c9FTD/ALS include toxicity from sense G C and antisense G C repeat-containing RNA, and from dipeptide repeat (DPR) proteins unconventionally translated from these RNA products. Intracerebroventricular injections with adeno-associated virus (AAV) encoding 2 or 149 G C repeats were performed on postnatal day 0, followed by assessment of behavioral and neuropathological phenotypes. Relative to control mice, gliosis and neurodegeneration accompanied by cognitive and motor deficits were observed in (G C ) mice by 6 months of age. Recapitulating key pathological hallmarks, we also demonstrate that sense and antisense RNA foci, inclusions of poly(GA), poly(GP), poly(GR), poly(PR), and poly(PA) DPR proteins, and inclusions of endogenous phosphorylated TDP-43 (pTDP-43) developed in (G C ) mice but not control (G C ) mice. Notably, proteins that play a role in the regulation of stress granules - RNA-protein assemblies that form in response to translational inhibition and that have been implicated in c9FTD/ALS pathogenesis - were mislocalized in (G C ) mice as early as 3 months of age. Specifically, we observed the abnormal deposition of stress granule components within inclusions immunopositive for poly(GR) and pTDP-43, as well as evidence of nucleocytoplasmic transport defects. Our in vivo model of c9FTD/ALS is the first to robustly recapitulate hallmark features derived from both sense and antisense C9orf72 repeat-associated transcripts complete with neurodegeneration and behavioral impairments. More importantly, the early appearance of persistent pathological stress granules prior to significant pTDP-43 deposition implicates an aberrant stress granule response as a key disease mechanism driving TDP-43 proteinopathy in c9FTD/ALS.